Digital Image Correlation for Cement-based Materials and Structural Concrete Testing - Asdam Tambusay; Benny Suryanto; Priyo Suprobo (Civil Engineering Dimension, 2020)
This paper presents the application of a low-cost digital image correlation (DIC) system for automated crack mapping. The system employed makes use of a conventional digital camera, a remote image recording controller, and an open-source digital image correlation MATLAB software Ncorr. To showcase the potential of the proposed system, two case studies involving general structural and material testing were undertaken. In the first series, the DIC system was used to study the fracture processes in a reinforced concrete beam and to investigate the influence of key input parameters on the spatial quality of strain maps obtained from the DIC analysis. In the second series, the application of the DIC method was expanded to assist in the study of complex multiple micro-crack formations in ductile cement composite testing. It is shown that the strain maps obtained from the DIC technique have a close resemblance to the actual crack patterns